Asymmetry in sprint running: Strength and performance interactions - Exell, T.; Gittoes, M.; Irwin, G.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Asymmetry in sprint running can influence performance and injury. The aim of this study was to investigate the interaction between asymmetry in sprint performance and lowerlimb strength. Ground reaction force data were collected from eight sprint runners whilst performing maximal effort squat jumps. Asymmetry during jump tests was compared with asymmetry of step responses and kinetic variables collected during maximal velocity sprint running trials. Significant positive correlations were reported between net ankle work in sprinting and peak force (r = 0.895) and peak power (0.761) during strength diagnostic jump tests. Results indicated individual athlete asymmetry profiles for both performance and strength asymmetry, suggesting that bilateral strength imbalances do not entirely account for asymmetry in performance variables during sprint running.